Actualization of Al-Ihsan Values in the Normativity of The Qur'an In Islamic Education At Darul Falah Boarding School Pagutan Mataram - Zulkarnain, Zulkarnain; Supian Humaidi, Ahmad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
Al-Quran is one of the main guidelines for Muslims to guide humans towards a good life in this world and in the hereafter. The Qur'an contains rules, concepts, information, rules, and basic teachings that are complex and comprehensive, both explicitly and implicitly. The purpose of this research is to find out and examine the actualization of Al-Ihsan values in the normativity of the Qur'an and to find out and explore the supporting and inhibiting factors in the actualization of al-Ihsan values in Islamic Education at Darul Falah Islamic Boarding School. This study is a field research with a qualitative approach. Data mining was carried out using observation techniques, in-depth interviews, and documentation studies. The research location chosen by the author is Darul Falah Islamic Boarding School. The techniques of data collection are using observation, interviews, and documentation. The results of this study are the actualization of Al-Ihsan's values in Islamic education at the Darul Falah Islamic Boarding School Pagutan Mataram was reflected in two aspects, namely Ihsan in Worship and Ihsan in social intercourse or muamalah. Strengthening the actualization of Ihsan in worship is carried out through habituation in performing worship in the hope that the students who are accustomed to doing the routine of worship will form the values of Ihsan in the students' personal and the case of muamalah, there are two forms of actualization of Ihsan in social interactions which are practiced in Islamic boarding schools. Darul Falah is doing good muamalah to teachers and colleagues in the form of polite speech, and commendable morals. Keywords: Actualization, Al-Ihsan, Islamic Education